Characterization of Chromosomal Instability in Glioblastoma - Balzano, Elisa; Di Tommaso, Elena; Antoccia, Antonio; Pelliccia, Franca; Giunta, Simona (Frontiers in Genetics, 2022)
Glioblastoma Multiforme (GBM) is a malignant tumor of the Central Nervous System (CNS). The poor prognosis of GBM due to resistance to therapy has been associated with high Chromosomal Instability (CIN). Replication stress is a major cause of CIN that manifests as chromosome rearrangements, fragility and breaks, including those cytologically expressed within specific chromosome regions named Common Fragile Site (CFSs). In this work, we characterized the expression of human CFSs in the Glioblastoma U-251 MG cell line upon treatment with the inhibitor of DNA Polymerase Alpha Aphidicolin (APH). We observed 52 gaps/breaks located within previously characterized CFSs. We found 17 to be CFSs in GBM cells upon treatment with APH, showing a frequency equal to at least 1% of the total gaps/breaks. We report that two CFSs localized to regions FRA2E (2p13/p12) and FRA2F (2q22) were only found in U-251 MG cells, but not lymphocytes or fibroblasts, after APH treatment. Notably, these glioblastoma-specific CFSs had a relatively high expression compared to the other CFSs with breakage frequency between ~ 7% and 9%. Presence of long genes, incomplete replication and delayed DNA synthesis during mitosis (MiDAS) after APH treatment suggest that impaired replication process may contribute to this loci-specific fragility in U-251 MG cells. Altogether, our work offers a characterization of Common Fragile Sites expression in Glioblastoma U-251 MG cells that may be further exploited for cytogenetic and clinical studies to advance our understanding of this incurable cancer.